THE CONTRIBUTIONS OF RURAL TOURISM DEVELOPMENT FROM TOURISM STAKEHOLDERS’ PERSPECTIVE: A CASE AT SUNGAI SEDIM AMENITY FOREST, KEDAH, MALAYSIA - Naqib Md Yunoh; Ida Nadia Hamidon, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Tree Top Walk (TTW) at Sungai Sedim Amenity Forest (SSAF) could best be promoted not only through its natural scenery but also as the world’s longest TTW that could only be experienced at SSAF. However, TTW have not been able to promote and attract an adequate number of tourists to SSAF and its performance is still lagging despite being considered the most valuable product in Malaysia. Although, extensive strategies have been carried out to promote the tourism industry in Kedah, little attention has been paid to strategize and develop SSAF. Hence, the development of rural tourism at SSAF has been dislocated as an unfulfilled promise in spilling over the income to tourism stakeholders besides providing indigenous people with employment. Thus, this study aims to explore the strengths and contributions of rural tourism development from tourism stakeholders’ perspective (local communities, local authorities, visitors, and operators). The key strengths and contributions indicated the need to focus on maintaining the tourism stakeholders’ perception derived from various tourism dimensions. One of the most significant issue that emerge from this study is that rural tourism has become an important developmental agenda for SSAF due to its potential for business activities, which may provide benefits to the communities.